Injuries to the Head and Face in Brazilian Adolescents and Teenagers Victims of Nonnatural Deaths - Cavalcanti, Alessandro Leite (J Forensic Odontostomatol, 2012)
This study aimed to evaluate the occurrence of injuries to the head and face in adolescent and teenager victims of non-natural deaths. A retrospective study was undertaken by the analysis of medical forensic reports obtained from medical forensic examinations performed at the Department of Forensic Medicine of the city of Campina Grande, PB, Brazil, between January 2003 and December 2007. From a total of 607 reports issued during this time span, the study sample consisted of 423 reports (69.6%) referring to adolescents and teenagers of both genders, aged 12 to 18 years, who were confirmed to have died from external causes. The causes of death were encoded according to the Chapter XX of the International Statistical Classification of Diseases and Related Health Problems (ICD-10). The majority of victims were 17 year old males (25.8%). Firearms (33.3%) and transport accidents (32.2%) were the most common causes of death, with boys showing a 3.7 times greater likelihood of getting killed by firearms than girls. There was statistically significant relationship between the occurrence of transport accidents and gender. The majority of victims (71.6%) presented with multiple injuries throughout the body. There was statistically significant relationship between the occurrence of transport accidents and the presence of multiple injuries. A high percentage of the victims presented with injuries to the head and face. There was statistically significant relationship between the occurrence of transport accidents and the presence of injury to the head. Fatal gunshot wounds and transport accidents were the main causes of death of male adolescents and teenagers. The victims presented with multiple injuries, especially to the head and face, and the mandible was the most frequently injured facial bone.